On the OPSF and the downstream oil industry deregulation: Lead us not into reversal temptation and deliver us from obfuscation - Adoracion M. Navarro (Philippine Institute for Development Studies (PIDS), 2022)
The recent calls for the revival of the Oil Price Stabilization Fund (OPSF) are tantamount to a call for a policy reversal, that is, reversal of the downstream oil industry deregulation that began in 1998. The history of the OPSF presents important lessons for policymakers. Petroleum price setting by fiat and using a price stabilization fund to smooth the price resulted in mismatches between payments to the fund and claims against it. The general public then ended up subsidizing oil consumers through subsidies from the national budget. When faced with political pressures, policymakers also lacked discipline in sticking to the price stabilization purpose of the OPSF, such as failing to implement the increase in the regulated price when the magnitude was large and allowing the use of the fund for something not directly related to price stabilization. Settling the legal challenges to OPSF credits and payments with finality also took time. Price distortion also resulted in cross-subsidization that created mismatches between demand and environmental objectives. Although there remain a few countries that have price stabilization funds, all of them are finding it hard to sustain funds operation and dealing with large deficits. Besides, the general direction of reforms globally is to remove fossil fuel subsidies. [...]
Keywords: 330; Oil Price Stabilization Fund; oil price regulation; downstream oil industry deregulation; policy reversal; oil crisis; targeted assistance; fossil fuel subsidies; price unbundling; oil stockpiling; strategic oil reserves